The Human Nasal Microbiome: A Perspective Study During the SARS-CoV-2 Pandemic in Malta - David Pinzauti; Simon De Jaegher; Maria D’Aguanno; Manuele Biazzo (Microorganisms)
The human respiratory tract is colonized by a complex microbial community that helps maintain respiratory health and plays a crucial role in defending the host from infections. Respiratory viruses have been demonstrated to alter microbiota composition, resulting in opportunistic species expansion, and increasing the disease severity and host susceptibility to bacterial co-infections. This study aims to examine the compositional differences in the nasal microbiota between SARS-CoV-2-infected and non-infected patients. We conducted Oxford Nanopore full-length 16S rRNA sequencing on nasal swabs from 94 COVID-19 negative and 85 COVID-19 positive patients collected during the SARS-CoV-2 pandemic in Malta. Our analysis identified significant alpha and beta diversity differences in the nasal microbiota composition among our study groups. We observed a trend toward decreased microbial richness and evenness in the COVID-Positive cohort with and increased abundance of common nasal opportunistic species including Citrobacter koseri, Dolosigranulum pigrum, Haemophilus influenzae, Klebsiella pneumoniae, and Moraxella catarrhalis. The findings from this study are in line with previously published papers identifying key alterations in the nasal microbiota composition associated with SARS-CoV-2 infection. Understanding these microbiome-driven mechanisms could present novel prognostic markers or offer new approaches for disease prevention and treatment.